IRP AND RENT, CAPITAL GAINS FROM PROPERTY LEASE - Amado Cardozo Paredes, Angel; Beatriz Mereles Ibarra, Diana; Rosalba Sánchez Bruno, Nilsa (Revista Gênero e Interdisciplinaridade, 2023)
This research work aims to demonstrate whether taxpayers comply with the tax formalities in the specific case, personal income tax, income category, capital gain from property lease, since it is important for taxpayers to know on the new current updates of the new tax reform law 6380/19 since it is important to know this data to improve formality and therefore seek solutions to the problems of our country. The approach used was quantitative, statistical data was obtained with more exact results, a descriptive investigation was planned, through closed surveys to know exactly what the real situation is in the formal field, resulting in a majority unaware of the new updates of the current regulations. It is important to note that most of the taxpayers of this tax obligation are not aware of or updated on the new tax reform, as there are also taxpayers with little interest in learning about it.